A survey of knowledge and attitudes relating to cervical and breast cancer among women in Ethiopia - Chaka, Bekele (BioMed Central, 2018)
Background: Breast cancer and cervical cancer are the two leading cancers among women in Ethiopia. This study investigated knowledge and attitudes related to these two types of cancer among women in 4 zones of Ethiopia. This is the first study employing a validated questionnaire to investigate knowledge and attitudes relating to breast and cervical cancer in Ethiopia. Methods: A community based cross-sectional study was conducted from September to November 2015 in the North Shewa zone (Amhara region), Gamo Gofa zone (Southern Nations, Nationalities and Peoples’ region) and zones 1 and 3 (Afar region) of Ethiopia. A total of 799 women aged 18 years and older participated in the survey. Multiple logistic regression analysis was used to investigate the association of possible predictors with breast and cervical cancer knowledge. Results: A total of 799 women aged 18 years and older participated in the survey. Of the women interviewed, 63.0% had heard of breast cancer and 42.2% had heard of cervical cancer. Among those who had heard of breast cancer, 21.3% (107/503) had heard of breast cancer screening and 1.4% of women aged 40 years and older had undergone at least one breast screening examination. Fewer than half of the participants provided the correct response to questions related to risk factors for breast and cervical cancer. Among those who had heard of cervical cancer, 41.5% (140/337) had heard of cervical cancer screening and 3.3% had undergone at least one cervical cancer screening examination. Women with primary and higher levels of education were more likely to have heard of breast cancers (OR = 3.0; 95% CI: 2.1–4.2; p < 0.001) and cervical cancer (OR = 1.9; 95% CI: 1.4–2.6; p < 0.001). From the overall attitude score, the majority of the women were found to have negative attitudes towards breast cancer (67.4%) and cervical cancer (70.6%). Conclusions: This study found that the overall knowledge of risk factors for breast cancer and cervical cancer among women was low. Lack of cancer awareness, and lack of education in general, are the most potent barriers to access and care, and should be addressed through multi-faceted strategies including peer-education, mass media and other community-based interventions.
Keywords: Breast cancer; Cervical cancer; Knowledge attitudes and beliefs; Ethiopia; MEDICINE::Surgery::Oncology; SDG-3: Good health and well-being